Severity of Allergic Rhinitis and Body Mass Index: Is There Any Correlation? - Paramasivam, Gomathi; Veronica, Fifi; Yoanita, Yovi (Althea Medical Journal, 2017)
Background: Allergic rhinitis is the inflammation of the nasal mucosa. It will be resulting in nasal itching, sneezing, discharge, or blockage which occurs for more than an hour on most days. Allergens such as plant pollens, fungi, animal allergens, and dust mites are the factors which initiate allergic rhinitis. There are many risk factors for allergic rhinitis, such as family history of atopic disease, asthma, age, gender and others. Besides, overweight is also considered one of the risk factors for developing allergic rhinitis. Thus, this study was conducted to investigate the correlation between allergic rhinitis and body mass index.Methods: This study involved a cross-sectional analytic study. Seventy three respondents both male and female medical students of Universitas Padjadjaran completed a questionnaire, and had their height and weight measured by a trained researcher. This study was carried out from September to October 2015. Statistical analyses were performed included the Rank Spearman test.Results: There was no significant relationship between allergic rhinitis and body mass index.Conclusions: There is no correlation between severity of allergic rhinitis and body mass index. [AMJ.2017;4(1):20â4]DOI:Â 10.15850/amj.v4n1.1018